Selection and characterization of DARPins against therapeutically relevant target proteins - Nyman, Paulus (My University, 2025)
DARPins (designed ankyrin repeat proteins) are small non-antibody binders. Their stability, high expression in prokaryotic cells, and lack of disulfide bridges make them interesting research topic for therapeutic and diagnostic use. In this study, a previously constructed DARPin library was screened against two target proteins with clinical significance (undisclosed, referred as X and Y). Phage display biopanning was used for isolating binders. The enrichment of binders was confirmed with phage immunoassay from total panning output and from individual clones. With four panning rounds, >50 % hit rate against X and >15 % against Y were achieved, when signal to background ratios over three were counted as hit. The best binders against X and Y showed S/B ratios over 400 and 250, respectively. That confirmed the success of selections. To create even stronger binders against target Y, DARPins from fourth round were combined with peptide linkers of multiple lengths. New bivalent library was screened with off-rate panning to select the strongest binders. Individual DARPins showing the highest binding in immunoassay were produced and the binding was characterized. Best binders for both X and Y had affinities in nanomolar range (<10 nM). Afterwards, validated binders could be taken into further development such as screened for functional properties against the target proteins. At this state, the study has proven the effectiveness of used library and methods for binder discovery, even against potentially challenging proteins. In the future, the pipeline could be used as a platform for early-stage drug development for multiple different targets.
Keywords: binder, biopanning, DARPin, drug development, epitope, phage display